TRADISI BUDAYA UPACARA BAYUH OTON SAPUH LEGER PADA MASYARAKAT HINDU BALI - MULYATI, PUTU (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
The Sapuh Leger ceremony is a traditional purification ritual in Balinese Hindu society, conducted for individuals born during the “Wuku Wayang” period, which is believed to hold a high spiritual significance. This ritual is thought to dispel negative influences and protect against disturbances from malevolent forces, particularly Bhuta Kala. Understanding this cultural practice through a biopsychosociospiritual approach is crucial to support the mental well-being of individuals within their cultural context. The Sapuh Leger ceremony is an integral part of Balinese culture, serving a spiritual healing function for individuals born during the Wuku Wayang period. The biopsychosociospiritual approach in this ritual highlights the importance of the connection between mental health and cultural heritage. This ceremony supports individuals in achieving well-being by involving the community, spiritual beliefs, and a purification process. The ritual not only wards off negative influences but also strengthens cultural and spiritual identity in the daily life of Balinese society. ABSTRAKUpacara Sapuh Leger adalah ritual penyucian tradisional dalam masyarakat Hindu Bali, yang dilakukan bagi individu yang lahir pada periode “Wuku Wayang” yang dianggap memiliki makna spiritual tinggi. Ritual ini diyakini dapat menghilangkan pengaruh buruk dan mencegah gangguan dari kekuatan negatif, khususnya Bhuta Kala. Praktik budaya ini penting untuk dipahami melalui pendekatan biopsikososiospiritual guna menjaga kesejahteraan mental individu dalam konteks budaya. Upacara Sapuh Leger adalah bagian integral dari budaya Bali yang memiliki fungsi penyembuhan spiritual bagi individu yang lahir pada Wuku Wayang. Pendekatan biopsikososiospiritual dalam ritual ini menekankan pentingnya keterhubungan antara kesehatan mental dan warisan budaya. Upacara ini mendukung individu dalam mencapai kesejahteraan dengan melibatkan komunitas, keyakinan spiritual, dan proses pembersihan. Ritual ini tidak hanya mencegah pengaruh negatif, tetapi juga memperkuat identitas budaya dan spiritual dalam keseharian masyarakat Bali.